(untitled) (Research, Society and Development, 2020)
Agribusiness is related to the economic vocation of Brazil due to climate, soil, water abundance, favorable relief, and the high insolation index with luminosity throughout the year. The productive chains in this segment represent approximately 30% of the gross domestic product, which makes Brazil the largest producer and exporter of different products of animal and plant origin. Forestry with planted forests makes Brazil the world’s largest producer and one of the main exporters of pulp, being Mato Grosso do Sul State a major producer with the highest growth of planted eucalyptus forests in the last 10 years. Academic studies available in the literature related to economic and managerial aspects do not cover more specifically small and medium rural properties that have been dedicated to forestry, especially to wood treatment and its strategic aspects. This study aims to propose a model for the analysis of strategic positioning in wood treatment companies. Methodologically, it is a non-probabilistic and intentional for convenience, exploratory and qualitative single case study. Interviews, visits to the company, and consultation of management and accounting documents were used as an instrument of data collection. Techniques already consolidated in the literature and market, such as Pestel analysis, Porter’s five forces, and SWOT analysis were used for conducting the strategic positioning analysis. The analysis results, however, are presented by means of a complete mapping of strategic positioning of the studied company and its strategies for the differentiation of its products and the effort to consolidate brand in an agricultural commodity. Study limitations are related to the difficulty of using it in other companies of the same business segment since it is a single case, but this fact does not invalidate the academic contributions. In this sense, new research lines are presented as the possibility of mapping brand consolidation in a forestry commodity and using forest residues from wood harvesting.